Effect of Lavender cream with or without footbath on anxiety, stress and depression of women in postpartum: A clinical randomized controlled trial - Fatemeh Effati Daryani; Sakineh Mohammad Alizadeh Charandabi; Somayeh Zarei; Azam Mohammadi; Mojgan Mirghafourvand (Mashhad University of Medical Sciences, 2017)
Introduction: Postpartum is a vulnerable period in terms of mental problems. Herbal medicine may be an effective intervention for improving the mothers' mental health.This study was performed with aim to determine the effect of Lavender cream with or without footbath on anxiety, stress and depression. Methods: This randomized clinical controlled trial was conducted on 141 women aged 18-40 years with first to three pregnancies at 25-28 weeks of pregnancy in Tabriz-Iran during 2013-2014. The subjects were placed in three groups; receiving Lavender cream and footbath, Lavender cream, and placebo. Immediately after delivery, women applied locally 2 gr (two segments of hand finger) cream (Lavender or placebo) to the legs, 1.5 hours before sleep, for 6 weeks. The group of footbath immersed their legs in warm water. Depression, anxiety and stress were assessed at baseline and 6 weeks after delivery using DASS-21 (Depression, Anxiety, stress scales-21). Data were analyzed by SPSS software (version 14) and One-way ANOVA, Kruskal-Wallis and Mann-Whitney U tests. P<0.05 was considered significant. Results: There was no significant difference between the three groups in terms of anxiety, depression and stress before intervention. There was significant difference between the three groups in terms of anxiety (P<0.001), stress (P<0.001) and depression (P<0.001) at 6th week postpartum; Mann-Whitney U test showed statistically significant difference between two intervention groups with the placebo group (P<0.05), but no significant difference was found between two intervention groups (P>0.05). Conclusion: Lavender cream with or without footbath can decrease stress, anxiety and depression of women at postpartum period.